Poetry in motion: catching molecules in action - Edward N. Baker (IUCrJ, 2024)
Researchers have long sought to `see' proteins and other macromolecules in motion, to better understand their functions. Technological developments, notably advances in serial crystallography, are now making these dreams a reality, heralding a new era of kinetic crystallography.